Prediction and Optimization of Damper Winding Structural Parameters for Salient-Pole Synchronous Generators With Rectifier Load - Meijun Qi; Jiakuan Xia; Le Kang; Menglin Song (IEEE Access)
Salient-pole synchronous generator with rectifier load has been widely used in aviation power system for its advantages of high DC power supply quality and strong fault tolerance. Damper winding directly affects the steady-state and transient performance of salient-pole synchronous generator. To study the impact of damper winding, a prediction and optimization method based on the combination of neural network approximation model and multi-objective optimization is proposed in this paper. Taking a salient-pole synchronous generator with uncontrolled rectifier load as the research object, the OLHD is carried out with five parameters of the number, radius, slot pitch angle, slot width and slot height of damper windings as design variables. The sensitivity of different design variables to the commutated reactance, THD of AC side voltage, DC side output voltage and its ripple factor, output torque are analyzed. Based on the OLHD results, EBF neural network approximation model is established. With the goal of optimizing the commutated reactance, THD, ripple factor, and ensuring DC side voltage and torque, the AMGA is used to optimize the design of the damper winding structure. Finally, finite element simulation is conducted to verify the feasibility and accuracy of the method.